Kajian Pemilihan Antinausea Dan Antivomiting Pada Penggunaan Antineoplastik Di Bangsal Bedah Pria Dan Wanita - Nofriyanti Nofriyanti (Jurnal Penelitian Farmasi Indonesia)
Cancer is the 2nd deadliest disease in the world after heart disease. Research to assess the election of anti nausea and anti -vomiting in cancer patients treated with antineoplastic and see the relationship between the emetogenic level of antineoplastic regimen on the incidence of nausea and vomiting experienced by patients hospitalized in the surgical ward. The study was observational descriptive cross-sectional design. Subject are all populations in accordance with the inclusion criteria, hospitalized cancer patients who use antinausea and anti-vomiting before administration of antineoplastic, interview and fill out the questionnaire in <24 hours after administration of antineoplastic to assess the degree of nausea/vomiting experienced. Intravenous ondansetron and dexamethasone are used by 31 patients and 2 people using just ondansetron. The use of HEC and MEC is a combination of ondansetron, dexamethasone, and aprepitant, while the use of LEC is just ondansetron. It can be concluded election of antinausea and anti-vomiting suited for nausea and vomiting due to the use of antineoplastic, but not in accordance with the emetogenic level of antineoplastic. Keyword : antinausea; antivomiting; antineoplastik; level emetogenic; cancer